A quasi-transient model of a transcritical carbon dioxide direct-expansion ground source heat pump for space and water heating. (5th December 2015) - Eslami-Nejad, Parham; Ouzzane, Mohamed; Aidoun, Zine
Abstract: In this study, a theoretical quasi-transient model is developed for detailed simulations of a carbon dioxide (CO2 ) direct-expansion ground source heat pump (DX-GSHP). This model combines a transient analytical model for the ground, steady-state numerical models for the borehole and the gas cooler, as well as several thermodynamic models for the remaining components of a conventional heat pump, organized in interacting subroutines to form a powerful simulation tool. Extensive validation combining experimental data and CFD-generated results was performed for the borehole before the tool was used to simulate a practical application case. Performance is investigated for a system satisfying both space heating and domestic hot water requirements of a typical single family detached home in a cold climate region. The variation of different system parameters is also evaluated in this study. It is shown that CO2 DX-GSHPs can offer relatively efficient and stable performance for integrated water and space heating applications. Furthermore, the importance of an accurate geothermal borehole sizing is highlighted for the DX-CO2 heat pump systems. It is shown that, due to changes in the system working conditions, the total borehole length is not linearly correlated with the heat pump energy consumption and other parameters such as heat pump coefficient of performance and pressure drop in ground heat exchangers. Results showed that increasing the total borehole length of an optimum design (reference case study) by 25% decreases the total annual energy consumption by only 6%. However, reducing total borehole length of the reference case by 25% increases the total annual energy consumption by 10%. Highlights: A quasi-transient model for CO2 direct-exchange ground-source heat pump is developed. Validation combining experimental data and CFD-generated results was performed. The effect of the borehole size on the design parameters is evaluated. Results show that borehole oversize has a marginal impact on the energy consumption.